Timimoun: The Cinema City in the Algerian Sahara From Caravan Crossings to Camera Crossings - An Analytical Reading - - Nawal, KERROUCHE (Journal of Ecohumanism, 2025)
Timimoun, designated as the cinema city at the heart of the Algerian desert, represents an ambitious project that bridges historical memory with contemporary visual creativity. The Caravan Khan Tower (Burj Khan al-Qawafil) serves as the central symbolic axis of this project, transforming from a traditional crossing point for commercial caravans into a passage for cameras and image-makers.This choice draws upon the region’s rich cultural heritage—including its distinctive mud-brick architecture, folk narratives, ritual practices, captivating natural landscapes, and the caravan routes that traversed the area across centuries—all of which reshape the desert space as a global cinematic filming platform.Through this initiative, Timimoun aspires to become an imagined civilizational space mediated through the screen, where cultural authenticity is leveraged to support a creative economy based on cinema and cultural tourism. The conversion of the Caravan Khan into a cinematic beacon represents a step toward constructing a contemporary visual narrative that reconnects the region’s past with its present via the art of moving images.